Answer:
See Below.
Step-by-step explanation:
We are given the two functions:
[tex]\displaystyle g(x) = 3x - 6 \text{ and } h(x) = 5x[/tex]
Part A)
Recall that:
[tex](g\cdot h)(x)=g(x)\cdot h(x)[/tex]
Substitute and simplify:
[tex]\displaystyle \begin{aligned} (g\cdot h)(x) & = (3x-6)\cdot(5x) \\ \\ &=5x(3x)-5x(6) \\ \\&=15x^2-30x \end{aligned}[/tex]
Part B)
Recall that:
[tex](g+h)(x)=g(x)+h(x)[/tex]
Substitute and simplify:
[tex]\displaystyle \begin{aligned} g(x) + h(x) & = (3x-6) + (5x) \\ \\ & = 8x- 6 \end{aligned}[/tex]
Part C)
Recall that:
[tex]\displaystyle (g-h)(x) = g(x) - h(x)[/tex]
Hence:
[tex]\displaystyle \begin{aligned} (g-h)(-1) & = g(-1) - h(-1) \\ \\ & = (3(-1)-6) - (5(-1)) \\ \\ & = (-9) + (5) \\ \\ & = -4\end{aligned}[/tex]